Kajian Kuat Lekat Pada Beton Variasi Limbah Granit Sebagai Substitusi Parsial Agregat Kasar - Fahmi Firman Maulana (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Infrastructure development contributes to increasing the competitiveness of domestic products, employment energy absorption, and regional growth. Therefore, a strong, rigid and stable construction is needed. The use of materials for construction needs to be considered, especially commonly used materials such as concrete. This research aims to analyze the effect of variations in granite content as a partial substitution for coarse aggregate on the bond strength of BRA (Concrete Recycled Aggregate) concrete. Experimental methods were used in this research. The concrete mix design uses a variety of granite waste with a content of 0%; 15%; 30%; and 45%. The test object used was a concrete cube with a side length of 20 cm. The bond strength of the concrete is tested using a Universal Testing Machine (UTM) and a dial gauge. Based on research, the maximum bond strength value is obtained at a granite content of 30%. The addition of granite waste causes an increase in the bond strength value. The bond strength value of concrete when slip occurs is 0.25 mm at 0% granite content; 15%; 30%; and 45% each valued at 14.61 MPa; 15.44 MPa; 18.62 MPa; and 17.15 MPa. Concrete bond strength value at maximum load at 0% granite content; 15%; 30%; and 45% each valued at 22.42 MPa; 22.59 MPa; 24.01 MPa; and 23.12 MPa.